2008
DOI: 10.1007/s10552-008-9176-z
|View full text |Cite
|
Sign up to set email alerts
|

Lesbians and cancer: an overlooked health disparity

Abstract: This review revealed a lack of research for specific cancers and for specific aspects of the cancer continuum. The limited number of studies identified focused on issues related to screening/prevention in cervical and breast cancers, with almost no attention to incidence, etiology, diagnosis, treatment, survival, morbidity, or mortality. We present implications for social and public health policy, research, and prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
81
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(81 citation statements)
references
References 69 publications
0
81
0
Order By: Relevance
“…However, researchers are increasingly recognizing that breast cancer affects all women, regardless of sexual orientation or marital or partnership status. Compared to heterosexual women, sexual minority women, defined as self-identified lesbian and bisexual women and those who prefer female partners [16], may have greater breast cancer risk factors [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], incidence [32], and mortality [33]. Thus, the exclusive focus of most breast cancer survivorship and caregiving research on heterosexual women and dyads carries important implications for the generalizability and translational utility of research findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, researchers are increasingly recognizing that breast cancer affects all women, regardless of sexual orientation or marital or partnership status. Compared to heterosexual women, sexual minority women, defined as self-identified lesbian and bisexual women and those who prefer female partners [16], may have greater breast cancer risk factors [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], incidence [32], and mortality [33]. Thus, the exclusive focus of most breast cancer survivorship and caregiving research on heterosexual women and dyads carries important implications for the generalizability and translational utility of research findings.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the scientific literature revealed a paucity of research related to any aspect of cervical cancer in lesbians. 49 A single study has provided some evidence that lesbians perceive themselves to be less susceptible to cervical cancer than heterosexual women, 50 although this finding has not been empirically confirmed. Other factors have been proposed as potential barriers to routine cervical cancer screening in lesbians.…”
Section: Discussionmentioning
confidence: 99%
“…Findings on medical breast cancer screening have been mixed, as observed in a recent review of health disparities among lesbians with cancer (Brown & Tracy, 2008). Whereas some studies found that lesbians were less likely than heterosexual women to have had a recent mammogram (e.g., Cochran et al, 2001) or clinical breast exam (Diamant, Wold, Spritzer, & Gelberg, 2000), another found lesbians were more likely to have had a recent mammogram (Aaron et al, 2001).…”
Section: Sexual Minority Women and Breast Cancer Researchmentioning
confidence: 99%